THE NOTION OF TRAUMA AND IDENTITY IN “THE AMERICAN PASTORAL” ABSTRACT - Khayrulloyeva Sitora Lutfulloyevna (Лучшие интеллектуальные исследования, 2023)
The term psychological novel has been widely used since the beginning of the twentieth century. One of the most outstanding representatives of the psychological fiction genre is Philip Roth. His one of the most famous works of all times "The American Pastoral" will be analyzed through the psycho-analytic method. The findings implies that the author tries to demonstrate the trauma in his characters, its aftermath by his own alter ego and the intergenerational trauma by the representation of Jewish minority group in US.